Kepastian Hukum Status Anak Karena Pembatalan Perkawinan dan Akibat Hukumnya Dalam Sistem Hukum Di Indonesia - Indah Sukma Ramdhini; Felicitas Sri Marniati; Yurisa Martanti (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
In carrying out a marriage, thereare conditions that must be carried out by the bride and the groom. who wants to marry in accordance with the marriage law and the law of their respective religions. If these conditions are not implemented,the marriage can be annulled. From the annulled marriage, there are children who are born, so how is the legal certainty and the legal consequences of the status of the children born from the canceled marriage. In this study, the theory of legal consequences is used, namely that a legal action taken by a legal subject can lead to a legal consequence and the theory of legal certainty is how the rules that are clear, issued and recognized by the state are used by judicial leaders who are carried out concretely. The method used in this research is normative juridical research, specifically a library law research or secondary data with primary, secondary and tertiary legal sources. As for the research approach used the statutory approach, the conceptual approach. The analytical approach and the method of collecting the legal materials are carried out by identifiying and taking an inventory of positive law, journals and other legal sources. The method used in analyzing the legal materials or legal material analysis techniques, it is carried out with grammatical legal interpretation, systematic interpretation, and legal construction methods. From the research results can be obtained that : (1) the legal consequences of annulment of marriage on the status of children born in the marriage are children still have a legal relationship with their parents (2) legal certainty on the status of children born in the marriage is still a legal child and cancellation marriage does not apply retroactively to the status of the child.